Relationship between complex feeding behavior and nutritional status of children aged 6-24 months - Syamsuddin, Sri Devi (Jurnal Konseling dan Pendidikan, 2025)
Introduction Some people who hold the view that a healthy baby is a fat baby, do not think that the fulfillment of nutrition is not measurable and will play a role in the occurrence of excessive feeding including the provision of complementary foods (MP ASI). The study aims to determine the relationship between the behavior of providing MP-ASI with the nutritional status of children aged 6-24 months in the Mandiri Village UPTD Tomoni Health Center, East Luwu Regency. Method This research was conducted in Desa Mandiri UPTD Puskesmas Tomoni. The quantitative research method used a cross-sectional approach, a sample of 50 infants aged 6-24 months with a sample technique using accidental sampling. The research instruments were questionnaires and anthropometric measurements. The data analysis technique used the chi-square test. Results The study showed that the Asyimp Sig (2Sided) obtained 0.000 (α<0.05 ) and it can be concluded that there is a significant relationship between the behavior of providing complementary feeding and the nutritional status of children aged 6-24 months in the Mandiri Village, UPTD Tomoni Health Center, East Luwu Regency. Conclusion that there is a significant relationship between the behavior of providing complementary feeding with the nutritional status of children aged 6-24 months . For this reason, researchers hope that this study can be used as a form of routine activity to increase students' insight into children's nutritional status.